FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA PENERBANG SIPIL DI BALAI KESEHATAN PENERBANGAN JAKARTA - Cindy Amalia Syabilah; Ida Wahyuni; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Profession as a civilian pilot was one of the most stressful occupations. The accident happened on air transportation largely was caused by human factors. The results of research on the impact of stress on job performance found that some accidents were attributable to personal failure and error was caused by the involvement of stress factors experienced by workers. The aim of this study was to analyze the factors associated with job stress in a civilian pilot. This was a explanatory research with cross sectional approach. The study was conducted through interviews with civilian aviators who were conducting a medical examination from August to September 2014, total of 79 civilian pilots were respondents in this research. Chi Square test was used to analyze the data. The result of the research were 57,1% of civilian pilots suffered mild stress and 34,1% severe work stress. From the statistical test can be obtained that there were a association between age (p value=0,001), association between working period (p value=0,002), association between flying hours (p value=0,001), association between marital status (p value=0,003), relation between role in organization (p value=0,011), and association between demand of the task (p value=0,001), and association between interpersonal relationship (p value=0,018) with work stress. The need for strict application of the limitation of pilot flight hours thus avoiding fatigue and stress which can be at risk of human error